The Poetics of Ruins in the Golden Age - Lara Garrido, José (Analecta Malacitana. Revista de la sección de Filología de la Facultad de Filosofía y Letras, 2021)
This article opens with some general reflections (both classical and contemporary) on the meaning of ruins, and then it addresses the need to devise explanatory paradigms about the different historical periods and poetical sequences. The article takes as its starting point the broad meaning of the concept in Spanish, together with the extensive bibliography existing in the international context, and it favours those studies published in the last decades, as well as those poetical texts and genres unexplored so far. By doing so, the article makes it possible to offer a different historical and exegetical organigram. Examining the data about different traditions and topoi, the article demarcates both the historical sections and the authorial inflections, and it provides a series of paradigms that reveal certain textual gaps in relevant writers and works that have been paid scant attention. The article also explores the far-reaching changes operating in the eighteenth century, including the new view of Rome, the presence of artificial ruins in the English garden, travel books, and the beginning of modern archaeology, resulting from the discoveries of Pompeii and Herculaneum.